Senat w systemie organów państwowych III RP w świetle projektów nowej konstytucji - Matuszewski, Lech (Wydział Prawa i Administracji UAM, 1996)
The author defines the role of the Senate in the Polish political system within the present legal regulations ( Act of Parliament of October 10, 1992), and discusses the problem of Senate elections as well as its constitutional place within the framework of the Seym (Diet), the President and Government. He goes on to analyse various proposals to the Senate question adopted by various political groups as well as those included in the future Constitution of the Third Republic. The author quotes the solutions adopted in other legal systems - not just countries of old democratic tradition, but the postcommunist ones as well.
The Senate in the system of state institutions of the Third Polish Republic as seen within the project of the new constitution